(untitled) (International journal of artificial intelligence, 2025)
This article examines the significance and content of visual arts education in primary school, highlighting its role in developing students’ creative thinking, imagination, and artistic abilities. The study emphasizes that the State Educational Standards require primary school teachers to foster learners’ cognitive development, communicative competence, emotional sensitivity, and aesthetic perception. The curriculum structure, which consists of four main sections - graphics, sculpture, painting, and composition - is analyzed with regard to the formation of key competencies such as communication, information literacy, self-development, civic engagement, and cultural awareness. Special attention is given to the pedagogical importance of observing nature, perceiving the environment, and applying these observations in artistic activities. The article also discusses how perceptual and compositional tasks contribute to expanding children’s artistic vision, shaping spatial imagination, and enhancing their ability to interpret the world through creative expression.